2002
DOI: 10.1007/s00404-002-0437-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A prospective, double-blind, randomized, placebo-controlled clinical trial of bromocriptin in clomiphene-resistant patients with polycystic ovary syndrome and normal prolactin level

Abstract: The only significant effect of long-term bromocriptin therapy in clomiphene citrate resistant polycystic ovary women was to lower the serum prolactin concentration. It was also concluded that 10-15% of patients with polycystic ovaries experienced occasional ovulatory cycles and pregnancy whether or not they were on treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Kubota et al [15] stated a lesser ovulation rate of 57.3% and pregnancy rate of 27% of infertile females that have euprolactinemia used CC and bromocriptine. Parsanezhad et al [16] evaluated that the influence of addition bromocriptine to CC in PCOS euprolactinemic females that resist CC, no significant difference in gestational rate and ovulation in the study group. However, there is only a significant effect of bromocriptine in lowering PRL [16].…”
Section: Discussionmentioning
confidence: 99%
“…Kubota et al [15] stated a lesser ovulation rate of 57.3% and pregnancy rate of 27% of infertile females that have euprolactinemia used CC and bromocriptine. Parsanezhad et al [16] evaluated that the influence of addition bromocriptine to CC in PCOS euprolactinemic females that resist CC, no significant difference in gestational rate and ovulation in the study group. However, there is only a significant effect of bromocriptine in lowering PRL [16].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments indicated a high PRL level conferred suppressive effects. Feltus et al (13) have shown PRL could activate the expression of 3b-hydroxysteroid dehydrogenase II, which is a terminal enzyme in the biosynthesis of P. Previous studies have showed oral bromocriptine could decrease the serum PRL level in healthy women, accompa nied by a marked decrease in the P level in the luteal phase (14). Additionally, corpus luteum insufficiency was also noted in the endometrial biopsy.…”
Section: Effects Of Transitory Hyperprolactinemia On the Pregnancy Inmentioning
confidence: 96%
“…In fact, bromocriptine administration has given no benefit in clomifene citrate-resistant PCOS patients with normal prolactin levels receiving 150 mg clomifene citrate (days 5-9) and bromocriptin continuously administrated at a dosage of 7.5 mg daily [97]. On the contrary, the use of cabergoline has been proved to improve ovarian response in hyperprolactinemic patients with PCOS candidates for treatment with gonadaotropins [98].…”
Section: Bromocriptinementioning
confidence: 97%